2016
DOI: 10.1186/s41479-016-0005-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between diagnosis and treatment of community-acquired pneumonia in children in various medical centres across Europe with the United States, United Kingdom and the World Health Organization guidelines

Abstract: BackgroundThe aim of this study was to review the current status and usage of guidelines in the diagnosis and treatment of community-acquired pneumonia (CAP) in European countries and to compare to established guidelines in the United States (US), United Kingdom (UK), and the World Health Organization (WHO).MethodsA questionnaire was developed and distributed by the Community-Acquired Pneumonia Paediatric Research Initiative (CAP-PRI) working group and distributed to medical centres across Europe.ResultsOut of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
10
0
4
Order By: Relevance
“…These analyses highlighted how, even now, adherence to guidelines is still low. On the other hand, Usonis and colleagues through a questionnaire developed and distributed by the CAP Pediatric Research Initiative (CAP-PRI) working group and distributed across Europe showed high adherence to CAP guidelines, with a high prescription rate of narrow-spectrum penicillin for inpatients (amoxicillin (32%) and ampicillin (37%)) and outpatients (amoxicillin (84%)) [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…These analyses highlighted how, even now, adherence to guidelines is still low. On the other hand, Usonis and colleagues through a questionnaire developed and distributed by the CAP Pediatric Research Initiative (CAP-PRI) working group and distributed across Europe showed high adherence to CAP guidelines, with a high prescription rate of narrow-spectrum penicillin for inpatients (amoxicillin (32%) and ampicillin (37%)) and outpatients (amoxicillin (84%)) [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…There are no validated CAP severity scores for children, and prognostic indicators are limited . Therefore, we anticipated high rates of inappropriate prescribing and estimated that approximately 50% of uncomplicated CAP would be treated with third‐generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…A large recent series of studies from the United States found staphylococcus infection in only 22/2533 of the LRTI cases (37). Vancomycin is indicated for S. aureus and rarely for highly resistant pneumococcal infection (38). Streptococcus pneumonia is the most common cause of bacterial pneumonia in all ages (39,40).…”
Section: Discussionmentioning
confidence: 99%